Induction of MASH in three-dimensional bioprinted human liver tissue. - Vaidehi Joshi; Dwayne Carter; Alice E Chen; Keith Murphy; J William Higgins; Mediha Gurel; Daisy Chilin Fuentes; Sara Brin Rosenthal; Kathleen M Fisch; Tatiana Kisseleva; David A Brenner (PLoS ONE)
Metabolic dysfunction-associated steatohepatitis (MASH), formerly known as nonalcoholic steatohepatitis (MASH), is a major risk factor for cirrhosis and hepatocellular carcinoma (HCC) and a leading cause of liver transplantation. MASH is caused by an accumulation of toxic fat molecules in the hepatocyte which leads to inflammation and fibrosis. Inadequate human "MASH in a dish" models have limited our advances in understanding MASH pathogenesis and in drug discovery. This study uses complex multicellular 3D bioprinting, combining hepatocytes with nonparenchymal cells in physiologically relevant cell ratios using biocompatible hydrogels to generate bioinks Bioprinted human liver tissues consisting of the four major cell types, (hepatocytes, liver endothelial cells, Kupffer cells, and hepatic stellate cells) are generated from cells purified from normal human livers, using this complex bioprinting platform. These liver tissues are incubated in a cocktail consisting of fatty acids, lipopolysaccharide (LPS), and fructose to produce a MASH phenotype in comparison to liver tissues incubated in control media. Furthermore, these bioprinted liver tissues are of sufficient size to undergo histological processing and immunohistchemistry comparable to classic clinical pathological analysis. The MASH liver tissues develop hepatocyte steatosis, inflammation, and fibrosis, in response to the MASH induction media. Additionally, the transcriptome of the MASH tissues differed significantly from the healthy tissues and more closely resembled the transcriptome of biopsies of MASH livers from patients Thus, this study has developed a MASH bioprinted liver tissue suitable for studies on pathophysiology and drug discovery.